Utility Theory And The Concept Of Maslahah In Islamic Economics - Yuman Firmansyah; Abdul Wahab; Sumar’in (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2024)
This article aims to analyze and build an Islamic economic order with noble character based on the Qur'an and Hadith. The emergence of Islamic economics to provide an explanation that the theory of utility has not touched the most basic principles and goals of Muslim consumers, namely in fulfilling their material and non-material needs, it is difficult to distinguish between wants and needs, and cannot avoid excessive behavior. So that this need has not been felt to be met in consumption activities called mashlahah. In Islamic principles, it is emphasized that every activity and every human being in economic activities can be characterized by their ability to do ihsan and fastabiqul khairat, uphold justice and not act arbitrarily, both for themselves and the surrounding environment. The characteristics of utility and maslahah in Islamic economics have characteristics, namely the principles of faith, morals and law (muamalah). This research is a literature research with a thematic method. The concept of utility or satisfaction is very different from the concept of maslahah or usefulness which is the goal in Islamic consumption. The concept of utility is very subject because it departs from the fulfillment of needs that are indeed subject. Meanwhile, the concept of maslahah is relatively more objective because it departs from the fulfillment of desires which is relatively more objective than needs. Within the framework of this theory, Islamic economic principles and activities must be the operational basis of Islamic financial institutions in Indonesia.